Phenomenological study on the psychological well-being of tahfiz students - Adzim, Afa Fauzul; Abdul Rahman Ahmad Badayai,; Syaidatun Nazirah Abu Zahrin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explored the psychological well-being of huffaz students which is a crucial factor in preparing them for higher education studies. A positive psychological trait refers to six dimensions, namely: self-acceptance, positive relationships with others, autonomy, environmental mastery, purpose in life, and personal-growth. This research used a phenomenological qualitative method for thematic analysis. Participants were five hafiz students selected through snowball sampling. The findings show that their motivation in memorizing the Qur'an was to adorn their parents with a crown of glory in the afterlife. This shows a direction and purpose in life that is oriented towards happiness and well-being in the afterlife together with everlasting goodness in the worldly life. The other psychological functions also reflect a desire to grow in becoming a better person, accept one’s strengths, weaknesses, the past, manage daily activities, self-autonomy and establish positive relationships with others. In addition, doing murojaah (Qur’anic recitation) can lead to a peaceful soul. The psychological well-being of tahfiz students is crucial in preparing them become exemplary students in the higher-learning institutions